Design and validation of the CADIS-G: a screening instrument for anxiety, depression, loneliness and anger in the older population - Ruiz-Sancho, Elena; Román, Francisco J.; Torices, Lucia; Sánchez-Escamilla, Francisco; Aguirre, Andrea; Rubio, Enrique; Cañada, Patricia; Rodríguez, Natalia; León, Leticia; Pérez-Nieto, Miguel Ángel; Redondo-Delgado, Marta (Frontiers in Psychiatry, 2025)
IntroductionThe assessment of psychological variables in older adults is often conducted using instruments that are not specifically designed for this population. Moreover, there are few screening tools that are effective for healthcare professionals in detecting emotional difficulties in older individuals. Therefore, the objective of this study was to design a questionnaire that can be used as a screening instrument to measure emotional distress in older individuals. A 12-item instrument (CADIS-G) with a 4-point Likert-type response scale was developed and tested for validity.Method186 older adults from eight residences and/or centers for older individuals in Spain. The participants completed, in addition to the 12-item CADIS-G, different instruments considered gold standards: Yesavage Geriatric Depression Scale (GDS-15), Geriatric Anxiety Inventory (GAI), State-Trait Anger Expression Inventory (STAXI-2) and UCLA Loneliness Scale. Exploratory factor analysis (EFA) was performed to study the dimensionality of the CADIS-G items.ResultsThe results showed that 10 of the 12 items of the CADIS-G grouped well with the theoretically proposed gold standard scales.DiscussionThe CADIS-G is a screening instrument that shows adequate psychometric properties to measure anxiety, depression, anger and loneliness in older people.